Determining factors of business success or failure of large family businesses in Brazil (Research, Society and Development, 2023)
Objective: To understand and describe large Brazilian family businesses and the main factors that contribute to their business success or failure, such as family and management relationships in conducting their business. Originality: We seek to contribute and fill gaps in theoretical and practical aspects aimed at identifying problems and mitigating operational risks that occur in family businesses, and in Brazil, studies and publications with an emphasis on the characteristics and particularities of family businesses are low and started only in the late 1990s, 30 years after the US and Europe. Methodology: After analyzing and interpreting the information, a qualitative and quantitative research was carried out, seeking to build historical and technical knowledge for its conclusions, supported by documentary research and case studies of 50 family businesses listed on the Stock Exchange of São Paulo, equivalent to 30% of the observed population of publicly traded family businesses, with panel data presented. Results: The causes of failure of large family businesses classified as “bad” are financial difficulties due to the market situation and management difficulties in 61% of the cases and 39% due to family disinterest in running the business, while the successful cases there is a family interest in monitoring the business and professional management. 76% have 1st and 2nd generations in the family management and 20% members of the 3rd generation and 4% are no longer family members.